Peptides from hydrolysate of lantern fish (Benthosema pterotum) proved neuroprotective in vitro and in vivo. (June 2016) - Chai, Huey-Jine; Wu, Chang-Jer; Yang, Shu-Han; Li, Tsung-Lin; Sun Pan, Bonnie
Highlights: Fish protein hydrolysate derived from Benthosema pterotum (BPH) possessed neuron protection activity. BPH protected SH-SY5Y neuron cells against H2 O2 -induced apoptosis. BPH ameliorated D-gal-induced deficit of memory and learning ability on ageing ICR mice. BPH is able to serve as nutraceutical for easing the ageing and/or age-related neurodegenerative diseases. Abstract: Benthosema pterotum is an underutilized deep-sea by-catch fish. Its protein hydrolysate (BPH) showed antioxidative activity. The BPH consisting of 13.2 mg/g of active peptides, Phe-Tyr-Tyr and Asp-Trp, significantly reduced H2 O2 -induced reactive oxygen species (ROS) and apoptotic cell death in human neuroblastoma SH-SY5Y cells through activation of intracellular antioxidant defence system. In Morris water-maze test, BPH was able to ameliorate memory and learning deficiency of D-galactose (D-gal)-induced neurodegenerative/ageing ICR mice. BPH-fed mice showed significantly lower levels of both D-gal-induced thiobarbituric acid reactive substances (TBARS) and endothelial nitric oxide synthase (eNOS), but higher levels of glucose-6-phosphate dehydrogenase (G6PDH) and brain-derived neurotrophy factor (BDNF) in brain of ageing mice in comparison to the control. In light of these results, BPH may be considered as a novel nutraceutical for easing the ageing and/or age-related neurodegenerative diseases.